Choice model analysis of the "pick any/n" type of binary data - Takane, Yoshio (Japanese psychological research, 1998)
In the “pick any/n” method, subjects are asked to choose any number of items from a list of n items according to some criterion. This kind of data can be analyzed as a special case of either multiple‐choice data or successive categories data where the number of response categories is limited to two. An item response model was proposed for the latter case, which is a combination of an unfolding model and a choice model. The marginal maximum‐likelihood estimation method was developed for parameter estimation to avoid incidental parameters, and an expectation‐maximization algorithm used for numerical optimization. Two examples of analysis are given to illustrate the proposed method, which we call MAXSC.